2016
DOI: 10.1007/s12185-016-2082-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological aspects of human immunodeficiency virus-associated plasmablastic lymphoma: analysis of 24 cases

Abstract: Plasmablastic lymphoma (PBL) is a rare AIDS-related malignancy with a poor prognosis. Little is known about this entity, and no standard treatment regimen has been defined. To establish an adequate treatment strategy, we investigated 24 cases of PBL arising in human immunodeficiency virus-positive individuals. Most of the patients were in the AIDS stage, with a median CD4 count of 67.5/µL. Lymph nodes (58 %), gastrointestinal tract (42 %), bone marrow (39 %), oral cavity (38 %), and CNS (18 %) were the most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…Most of the oral PBL presented as asymptomatic swellings, frequently associated with ulcerations and bleeding. B‐symptoms were absent in most cases, suggesting a more local involvement of the disease in most of the cases, what is consistent with the large number of cases classified as Ann Arbor stage I, although stage IV diseases were also frequent . A previous review of 228 cases of PBL also revealed a similar result, although the majority of cases involved extraoral sites …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Most of the oral PBL presented as asymptomatic swellings, frequently associated with ulcerations and bleeding. B‐symptoms were absent in most cases, suggesting a more local involvement of the disease in most of the cases, what is consistent with the large number of cases classified as Ann Arbor stage I, although stage IV diseases were also frequent . A previous review of 228 cases of PBL also revealed a similar result, although the majority of cases involved extraoral sites …”
Section: Discussionsupporting
confidence: 81%
“…The low survival rates found for oral PBL were similar to the reported previously when all sites were considered . Nevertheless, prognostic factors described by previous studies that investigated PBL of different anatomical locations needs to be validated for tumors manifesting in the oral cavity and gnathic bones, what is especially difficult due to the limited number of cases available …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The CD10 positivity noted in some cases (35.3%) reflects that previously described in PBL (42%, 56%, and 67%) . CD10‐positive cases expressed markers of plasma cell differentiation: all cases expressed VS38c and/or MUM1/IRF4, and 50% expressed BLIMP1.…”
Section: Discussionsupporting
confidence: 70%
“…2,20,34 The CD10 positivity noted in some cases (35.3%) reflects that previously described in PBL (42%, 56%, and 67%). 29,35,36 CD10-positive cases expressed markers of plasma cell differentiation: all cases expressed VS38c and/or MUM1/IRF4, and 50% expressed BLIMP1. The occasional CD3 positivity (n = 2), regarded as aberrant, has been rarely described in DLBCL and PBL.…”
Section: Discussionmentioning
confidence: 97%